2017
DOI: 10.1159/000457130
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Associated Urogenital Malignancies

Abstract: Non-AIDS-defining malignancies (NADM) are a leading cause of morbidity and mortality for HIV-infected subjects. The risk of testicular germ cell cancer (GCC) and renal cell cancer is slightly increased in the setting of HIV, whereas there is a slightly decreased risk of prostate cancer and bladder cancer. As in industrialized countries the majority of people living with HIV are men, and people aged 55 and older now account for more than a quarter of persons living with HIV, both testis and prostate cancer are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Particularly for Human-immunodeficiency virus (HIV), authors first identified a pooled OR of 1.79 (94). This evidence was subsequently confirmed by several studies showing a relative risk ranging from 0.7 to 3.1 [reviewed in Hentrich and Pfister (95)]. However, as for EBV, a clear mechanistic model explaining the association between TC and HIV is currently under debate.…”
Section: Environmentmentioning
confidence: 71%
“…Particularly for Human-immunodeficiency virus (HIV), authors first identified a pooled OR of 1.79 (94). This evidence was subsequently confirmed by several studies showing a relative risk ranging from 0.7 to 3.1 [reviewed in Hentrich and Pfister (95)]. However, as for EBV, a clear mechanistic model explaining the association between TC and HIV is currently under debate.…”
Section: Environmentmentioning
confidence: 71%
“…Testis cancer, in particular seminoma and extragonadal germ cell cancer occur with a slightly greater risk in HIV-infected patients, without relation to CD4 count (two large series with 34 and 35 patients each one, reported the median CD4 count at cancer diagnosis was 325 and 315 cells/µL, respectively) [ 27 ]. Germ-cell tumors ranked third in frequency in males in our series (10.7%); mean age was 33 years, similar to the age reported in general population (25–45 years).…”
Section: Discussionmentioning
confidence: 99%
“…In Western countries, the majority of HIV-infected people are men, thus explaining why the incidence of testicular cancer is also increased in men with HIV [75]. In a 2017 review, Hentrich showed that seminoma and extragonadal germ cell cancer are more frequent in HIV-infected patients, whereas the risk for nonseminoma was marginally increased [76]. In the same way, HPV is closely linked with infertility in males and the role of this virus in testicular carcinogenesis cannot be excluded [66].…”
Section: Testicular Cancer (Tc)mentioning
confidence: 99%